Frequency and Risk Factors Associated with Musculoskeletal Pain among the Medical Students of Rawalpindi - Hisam, Aliya; Mashhadi, Syed Fawad; Raja, Amna Kaneez Fatima; Hamza, Muhammad Ameer; Sabir, Rida; Naveed, Tahoora; Umer, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find the frequency and risk factors associated with musculoskeletal pain (MSP) among the medical students of Rawalpindi. Study Design: Analytical cross-sectional studyPlace and Duration of Study: Army Medical College students, Rawalpindi Pakistan, were enrolled from Mar 2022 to Jul 2022.Methodology: An online, self-administered, altered version of the standardized Nordic Questionnaire was distributed among the students of Army Medical College, Foundation Medical University and Rawalpindi Medical University. Data were analyzed using IBM SPSS-25. Frequencies and means were calculated. Chi-square test and student’s t test were done to find any significant associations with p-value